(untitled) (Journal of the College of Education for Women, 2019)
This work represents development and implementation a programmable model for evaluating pumping technique and spectroscopic properties of solid state laser, as well as designing and constructing a suitable software program to simulate this techniques . A study of a new approach for Diode Pumped Solid State Laser systems (DPSSL), to build the optimum path technology and to manufacture a new solid state laser gain medium. From this model the threshold input power, output power optimum transmission, slop efficiency and available power were predicted. different systems configuration of diode pumped solid state laser for side pumping, end pump method using different shape type (rod,slab,disk) three main parameters are (energy transfer efficiency (rfac) and output coupler reflectivity (Roc) and spotshape) had been studied. The spectral distribution was measured with bandwidth 26nm.Optical pumped analysis, which used pump source input pump power 100mW increased to 700mW step 100mw .